Active material, negative electrode layer, battery pack, and method for producing same

By using silicon inclusion-type active materials with specific void structures in the battery pack, the problem of large volume changes in silicon during charging and discharging is solved, and a more stable battery pack and higher energy density is achieved.

CN119174017APending Publication Date: 2024-12-20TOYOTA JIDOSHA KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039091.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-03-14
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Silicon will cause large volume changes during the charging and discharging of the battery pack, affecting the stability and energy density of the battery.

Method used

A novel active material has been developed with voids in primary particles, a void volume X with a pore size of less than or equal to 10 nm and a type II silicon inclusion was observed by CuKα ray X-ray diffraction measurement The crystalline phase is used to reduce volume changes caused by charging and discharging.

Benefits of technology

The volume changes caused by charging and discharging are effectively suppressed, the stability and energy density of the battery pack are improved, and the confining pressure applied to the all-solid-state battery pack is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174017A_ABST
    Figure CN119174017A_ABST
Patent Text Reader

Abstract

An active material includes silicon. The active material has voids within the primary particles, and the void volume X of voids having a pore size of less than or equal to 10 nm in the voids is greater than or equal to 0.015 cc / g.
Need to check novelty before this filing date? Find Prior Art

Description

Background of the Invention Technical Field

[0001] The present disclosure relates to active materials, negative electrode layers, batteries, and methods of producing the active materials, negative electrode layers, and batteries. Related technical description

[0002] Battery packs have been actively developed in recent years. For example, in the automotive industry, battery packs for pure electric vehicles (BEVs) or hybrid electric vehicles (HEVs) have been developed. Silicon (Si) is a known active material for battery packs.

[0003] For example, Japanese Unexamined Patent Application Publication No. 2017-059534 (JP 2017-059534A) discloses an all-solid-state battery system containing alloyed negative electrode active material particles such as silicon particles. U.S. Patent Application Publication No. 2012 / 0021283 discloses that, by calculation, silicon clathrate can be used as a negative electrode active material in a lithium-ion battery pack. Japanese Unexamined Patent Application Publication Nos. 2021-158003 (JP 2021-158003 A) and 2021-158004 (JP 2021-158004 A) each disclose an active material having a crystalline phase of a type II silicon clathrate and voids within a primary particle. Summary of the invention

[0004] The theoretical capacity of Si is large, so Si is effective in increasing the energy density of a battery pack. However, Si undergoes a large volume change during charging and discharging.

[0005] The present disclosure provides an active material having a small volume change caused by charge and discharge.

[0006] The active material according to the first aspect of the present invention includes silicon. The active material has voids in primary particles, and the void volume X of the voids having a pore diameter of 10 nm or less in the voids is 0.015 cc / g or more.

[0007] In the active material according to the first aspect, the void volume X may be less than or equal to 0.09 cc / g.

[0008] In the active material according to the first aspect, the void volume Y of the voids having a pore diameter of 50 nm or less in the voids may be greater than or equal to 0.05 cc / g and less than or equal to 0.25 cc / g.

[0009] In the active material according to the first aspect, a ratio (X / Y) of the void volume X to the void volume Y may be greater than or equal to 0.17 and less than or equal to 0.41.

[0010] In the active material according to the first aspect, the void volume Z of the voids having a pore diameter of 100 nm or less in the voids may be greater than or equal to 0.05 cc / g and less than or equal to 0.40 cc / g.

[0011] In the active material according to the first aspect, a ratio (X / Z) of the void volume X to the void volume Z may be greater than or equal to 0.10 and less than or equal to 0.34.

[0012] The active material according to the first aspect may have a crystalline phase of type II silicon clathrate.

[0013] In the active material according to the first aspect, in the X-ray diffraction measurement using CuKα rays, a peak A at 2θ=20.09°±0.50° and a peak B at 2θ=31.72°±0.50° can be observed as peaks of the crystalline phase of the type II silicon inclusion compound. When the intensity of the peak A is I A , the intensity of peak B is I B , and the maximum intensity at 2θ = 22° to 23° is I M When A / I M may be greater than or equal to 1.75 and less than or equal to 10, and I B / I M It can be greater than or equal to 1.35 and less than or equal to 7.

[0014] The active material according to the first aspect may have a crystal phase of diamond-like silicon.

[0015] The negative electrode layer according to the second aspect of the present disclosure includes an active material containing silicon. The active material has voids in primary particles, and the void volume P of the voids having a pore diameter of 10 nm or less is 0.015 cc / g or more.

[0016] In the negative electrode layer according to the second aspect, the void volume P may be less than or equal to 0.031 cc / g.

[0017] In the negative electrode layer according to the second aspect, the void volume Q of voids having a pore diameter of 50 nm or less in the voids may be 0.035 cc / g or more and 0.11 cc / g or less.

[0018] In the negative electrode layer according to the second aspect, a ratio (P / Q) of the void volume P to the void volume Q may be greater than or equal to 0.22 and less than or equal to 0.39.

[0019] In the negative electrode layer according to the second aspect, the void volume R of the voids having a pore diameter of 100 nm or less in the voids may be greater than or equal to 0.053 cc / g and less than or equal to 0.16 cc / g.

[0020] In the negative electrode layer according to the second aspect, a ratio (P / R) of the void volume P to the void volume R may be greater than or equal to 0.14 and less than or equal to 0.30.

[0021] A battery pack according to a third aspect of the present disclosure includes the negative electrode layer according to the second aspect. The battery pack further includes a positive electrode layer and an electrolyte layer provided between the positive electrode layer and the negative electrode layer.

[0022] In a fourth aspect of the present disclosure, a method for producing an active material according to the first aspect includes obtaining a Na-Si alloy by reacting a sodium source and a silicon source with each other, and producing a silicon inclusion type crystalline phase by heating the Na-Si alloy to reduce the amount of sodium in the Na-Si alloy. The production of the silicon inclusion type crystalline phase uses a scavenger to remove sodium from the Na-Si alloy.

[0023] A method for producing a negative electrode layer according to a fifth aspect of the present disclosure includes producing an active material by the method for producing an active material according to the fourth aspect. The method further includes forming a negative electrode layer using the active material.

[0024] A method of producing a battery pack according to a sixth aspect of the present disclosure includes producing an active material by the method of producing an active material according to the fourth aspect. The method further includes forming a negative electrode layer using the active material.

[0025] The present disclosure produces an effect in that an active material having a small volume change caused by charge and discharge can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention are described below with reference to the accompanying drawings, in which like symbols refer to like elements, and in which: Figure 1A is a schematic perspective view illustrating a crystal phase of a type II silicon inclusion compound; Figure 1B is a schematic perspective view illustrating a crystal phase of diamond-type silicon; Figure 2 is a schematic cross-sectional view illustrating one example of a battery pack in the present disclosure; and Figure 3 is a flow chart illustrating one example of a method for producing an active material in the present disclosure. DETAILED DESCRIPTION

[0027] Hereinafter, a detailed description will be given of an active material, a negative electrode layer, a battery pack, and methods of producing the active material, the negative electrode layer, and the battery pack according to the present disclosure. A. Active Materials

[0028] The active material in the present disclosure contains silicon (Si), has voids within primary particles, and the void volume X of the voids having a pore diameter of 10 nm or less is large.

[0029] According to the present disclosure, the void volume X is large, so the volume change of the active material caused by charging and discharging is small. The inventors of the present invention have found in their research to date that by increasing the void volume Z of micro-voids with a pore size of less than or equal to 100nm, the void crushing caused by pressing is suppressed. In addition, the inventors of the present invention have found that by increasing the void volume Y of micro-voids with a pore size of less than or equal to 50nm, the void crushing caused by pressing is significantly suppressed. As a result of further research, the inventors of the present invention have found that, similar to micro-voids with a pore size of less than or equal to 50nm, micro-voids with a pore size of less than or equal to 10nm can significantly suppress the void crushing caused by pressing and effectively suppress the volume change caused by charging and discharging. Specifically, the void volume X of micro-voids with a pore size of less than or equal to 10nm is increased to increase the filling rate of deposited lithium (Li) in the void, thereby effectively suppressing the volume change caused by charging and discharging.

[0030] The shape of the active material in the present disclosure is generally microparticles. The active material can be a primary particle, or a secondary particle that is an agglomerate of primary particles. In either case, the primary particle generally has a void inside.

[0031] The active material in the present disclosure preferably has many tiny voids with a pore size of less than or equal to 10 nm. Compared with voids with a pore size greater than 10 nm, voids with a pore size of less than or equal to 10 nm can suppress the increase of confining pressure (confining pressure) because the deposited Li can be accommodated at a higher filling rate. The void volume (cumulative pore volume) X of the void with a pore size of less than or equal to 10 nm is, for example, greater than or equal to 0.015 cc / g, and may be greater than or equal to 0.0167 cc / g, greater than or equal to 0.020 cc / g, greater than or equal to 0.023 cc / g, or greater than 0.0337 cc / g. The void volume X is, for example, less than or equal to 0.09 cc / g. The void volume X can be measured by, for example, mercury porosimetry, Brunauer Emmett Teller (BET) measurement, gas adsorption, three-dimensional scanning electron microscopy (3D-SEM) or three-dimensional transmission electron microscopy (3D-TEM). The same applies to methods for measuring void volumes other than void volume X.

[0032] The active material in the present disclosure preferably has many tiny voids with a pore size of less than or equal to 50 nm. Compared with voids with a pore size greater than 50 nm and less than or equal to 100 nm, voids with a pore size of less than or equal to 50 nm can further suppress the void crushing caused by pressing. The void volume Y of the void with a pore size less than or equal to 50 nm is, for example, greater than or equal to 0.05 cc / g, and may be greater than 0.065 cc / g, greater than or equal to 0.072 cc / g, greater than or equal to 0.083 cc / g, or greater than or equal to 0.10 cc / g. The void volume Y is, for example, less than or equal to 0.25 cc / g, and may be less than or equal to 0.22 cc / g.

[0033] The ratio (X / Y) of void volume X to void volume Y is preferably large. The ratio X / Y is, for example, greater than or equal to 0.17, and may be greater than or equal to 0.19, or greater than or equal to 0.21. The ratio X / Y is, for example, less than or equal to 0.41.

[0034] The active material in the present disclosure preferably has many tiny voids with a pore size of less than or equal to 100 nm. Compared with voids with a pore size greater than 100 nm, voids with a pore size of less than or equal to 100 nm can suppress void crushing caused by pressing. The void volume Z of a void with a pore size of less than or equal to 100 nm is, for example, greater than or equal to 0.05 cc / g, and may be greater than or equal to 0.07 cc / g, greater than or equal to 0.10 cc / g, or greater than or equal to 0.12 cc / g. The void volume Z is, for example, less than or equal to 0.40 cc / g, and may be less than or equal to 0.39 cc / g, or less than or equal to 0.35 cc / g.

[0035] The ratio (X / Z) of the void volume X to the void volume Z is preferably large. The ratio X / Z is, for example, greater than or equal to 0.10, and may be greater than or equal to 0.14, or greater than or equal to 0.16. The ratio X / Z is, for example, less than or equal to 0.34.

[0036] The active material in the present disclosure has a void in the primary particle. The void ratio is, for example, greater than or equal to 4%, and may be greater than or equal to 10%. The void ratio is, for example, less than or equal to 40%, and may be less than or equal to 20%. The void ratio can be determined, for example, by the following procedure. First, the electrode layer containing the active material is sliced ​​by ion milling. Then, the particles are photographed by observing the cross section with a scanning electron microscope (SEM). The resulting photograph is distinguished from the silicon part and the void part by using image analysis software and binarized. The area of ​​the silicon part and the void part is measured, and the void ratio (%) is calculated by the following expression. Void ratio (%) = 100 × (area of ​​void portion) / ((area of ​​silicon portion) + (area of ​​void portion))

[0037] Specific image analysis and void fraction calculation can be performed as follows. For example, Fiji ImageJ (hereinafter referred to as "Fiji") bundled with Java 1.8.0_172 is used as image analysis software. The secondary electron image and the backscattered electron image in the same field of view are synthesized to form an RGB color image. The resulting RGB image is then blurred in Fiji by the function "median (filter size = 2)" to remove noise pixel by pixel. Next, the silicon portion and the void portion in the SEM image are separately brushed using Fiji, and the void volume is calculated by the area ratio between the silicon portion and the void portion.

[0038] With respect to RGB color imaging, both the secondary electron image and the backscattered electron image are represented in grayscale. Thus, for example, the brightness x of each pixel in the secondary electron image is set to a red value, while the brightness y of each pixel in the backscattered electron image is set to a green value. As a result, an RGB image is obtained in which, for example, R=x, G=y, and B=(x+y) / 2 are obtained in each pixel.

[0039] The average particle size of primary particles (D 50 ) is, for example, greater than or equal to 50 nm, and may be greater than or equal to 100 nm, or greater than or equal to 150 nm. The average particle size (D 50 ) is, for example, less than or equal to 3000 nm, and may be less than or equal to 1500 nm, or less than or equal to 1000 nm. The average particle size (D 50 ) is, for example, greater than or equal to 1 μm, and may be greater than or equal to 2 μm, or greater than or equal to 5 μm. The average particle size (D 50 ) is, for example, less than or equal to 60 μm, and may be less than or equal to 40 μm. The average particle size (D 50 ) can be measured by, for example, SEM observation. The number of samples is preferably large. For example, the number of samples is greater than or equal to 20, and can be greater than or equal to 50, or greater than or equal to 100.

[0040] The active material in the present disclosure preferably has a silicon inclusion compound type crystalline phase. The silicon inclusion compound type crystalline phase may be a crystalline phase of a type I silicon inclusion compound or a crystalline phase of a type II silicon inclusion compound. For example, Figure 1AType II silicon inclusion complex is shown. In such a silicon inclusion complex type crystalline phase, multiple Si elements form a polyhedron (cage) including pentagons or hexagons. The polyhedron has an internal space that can accommodate metal ions such as Li ions. By inserting metal ions into these spaces, the volume change caused by charging and discharging can be suppressed. In particular, in all-solid-state battery packs, high confining pressures must usually be applied to suppress the volume change caused by charging and discharging. By using the active material in the present disclosure, it is possible to reduce the confining pressure applied to the all-solid-state battery pack. Therefore, it is possible to suppress the increase in the size of the confining jig.

[0041] The active material in the present disclosure may or may not have a crystalline phase of a type II silicon inclusion compound. When the active material has a crystalline phase of a type II silicon inclusion compound, the active material may have a crystalline phase of a type II silicon inclusion compound as a main phase. "Main phase" means that the peak belonging to the crystalline phase has the highest diffraction intensity among the peaks observed by X-ray diffraction measurement. The phrase "not having a crystalline phase" means that the peak of the crystalline phase is not observed in the X-ray diffraction measurement.

[0042] The crystalline phase of type II silicon inclusion complex generally belongs to the space group (Fd-3m). In the X-ray diffraction measurement using CuKα rays, the crystalline phase of type II silicon inclusion complex has typical peaks at positions of 2θ=20.09°, 21.00°, 26.51°, 31.72°, 36.26° and 53.01°. These peak positions may vary within the range of ±0.50°, ±0.30° or ±0.10°.

[0043] In the crystalline phase of the type II silicon inclusion compound, the peak at 2θ=20.09°±0.50° is peak A, and the peak at 2θ=31.72°±0.50° is peak B. The intensity of peak A is given by I A Indicates that the intensity of peak B is expressed by I B The maximum intensity at 2θ = 22° to 23° is represented by I M The range of 2θ=22° to 23° is generally a range in which a peak of a crystalline phase related to Si does not exist. Therefore, it can be used as a reference.

[0044] I A / I M The value of is preferably greater than 1. A / I M When the value of is less than or equal to 1, it can be determined that substantially no crystalline phase of type II silicon inclusion compound is formed. A / I M The value of is, for example, greater than or equal to 1.75, and may be greater than or equal to 1.80. A / I MThe value of is, for example, less than or equal to 10, and may be less than or equal to 5.

[0045] I B / I M The value of is preferably greater than 1. B / I M When the value of is less than or equal to 1, it can be determined that substantially no crystalline phase of type II silicon inclusion compound is formed. B / I M The value of is, for example, greater than or equal to 1.35, and may be greater than or equal to 1.40. B / I M The value of is, for example, less than or equal to 7, and may be less than or equal to 4.

[0046] The active material in the present disclosure may or may not have a crystalline phase of a type I silicon inclusion compound. When the active material has a crystalline phase of a type I silicon inclusion compound, the active material may have a crystalline phase of a type I silicon inclusion compound as the main phase. The crystalline phase of the type I silicon inclusion compound generally belongs to the space group (Pm-3n). In an X-ray diffraction measurement using CuKα rays, the crystalline phase of the type I silicon inclusion compound has typical peaks at positions of 2θ=19.44°, 21.32°, 30.33°, 31.60°, 32.82°, 36.29°, 52.39° and 55.49°. These peak positions may vary within the range of ±0.50°, ±0.30° or ±0.10°.

[0047] The active material in the present disclosure may or may not have a diamond-type Si crystalline phase. Figure 1B As shown in , in the diamond-type Si crystalline phase, multiple Si elements form tetrahedrons. The tetrahedron does not have an internal space that can accommodate metal ions such as Li ions. Therefore, compared with the silicon inclusion compound type crystalline phase, the diamond-type Si crystalline phase is less likely to suppress the volume change caused by charging and discharging. The structural stability of the diamond-type Si crystalline phase is higher than that of the silicon inclusion compound type crystalline phase.

[0048] The active material in the present disclosure may have a diamond-type Si crystalline phase as a main phase. In X-ray diffraction measurement using CuKα rays, the diamond-type Si crystalline phase has typical peaks at positions of 2θ=28.44°, 47.31°, 56.10°, 69.17°, and 76.37°. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°.

[0049] When the peak C at 2θ = 28.44° ± 0.50° is observed as the peak of the diamond-type Si crystalline phase, the intensity of the peak C is determined by I C Indicates. A / I CThe value of is, for example, greater than 1, and may be greater than or equal to 1.5, greater than or equal to 2, or greater than or equal to 3. B / I C The preferred range of I A / I C The preferred range is the same.

[0050] Although the composition of the active material in the present disclosure is not particularly limited, it is preferably composed of Na x Si 136 (0≤x≤24). The value x may be 0 or greater than 0. The value x may be less than or equal to 20, less than or equal to 10, or less than or equal to 5. The active material in the present disclosure may contain inevitable components (e.g., Li). The composition of the active material may be determined by, for example, energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF), inductively coupled plasma (ICP), or atomic absorption spectroscopy. The composition of other compounds can be measured similarly. An inevitable oxide film is usually formed on the surface of the active material. Therefore, the active material may contain trace amounts of oxygen (O). The active material may also contain trace amounts of carbon (C) derived from the production process.

[0051] The active material in the present disclosure is generally used for a battery pack. The active material in the present disclosure may be a negative electrode active material or a positive electrode active material, but is preferably a negative electrode active material. The present disclosure may also provide an electrode layer (negative electrode layer or positive electrode layer) including the above-mentioned active material, and a battery pack including the electrode layer. Examples of methods for producing active materials include the production methods described later in "D. Methods for producing active materials". B. Negative electrode layer

[0052] The negative electrode layer in the present disclosure contains the above-mentioned active material.

[0053] According to the present disclosure, the negative electrode layer has a small volume change caused by charge and discharge by using the above-mentioned active material.

[0054] The negative electrode layer contains at least a negative electrode active material. The negative electrode active material is the same as described above in "A. Active Material". When the negative electrode layer is produced by pressing, the voids within the primary particles of the negative electrode active material may be crushed. When the void volume Z of the voids having a pore size of less than or equal to 100 nm in the negative electrode active material before pressing is large, the void crushing caused by pressing is suppressed. When the void volume Y of the voids having a pore size of less than or equal to 50 nm is large, the void crushing caused by pressing is further suppressed. Since the voids having a pore size of less than or equal to 10 nm can accommodate the deposited Li at a high filling rate, when the void volume X is large, the increase in confining pressure is suppressed.

[0055] The negative electrode active material contained in the negative electrode layer preferably has many tiny voids with a pore size of less than or equal to 10 nm. The void volume P of the voids with a pore size of less than or equal to 10 nm is, for example, greater than or equal to 0.015 cc / g, and may be greater than or equal to 0.017 cc / g, or greater than or equal to 0.019 cc / g. The void volume P is, for example, less than or equal to 0.031 cc / g.

[0056] The negative electrode active material contained in the negative electrode layer preferably has many tiny voids with a pore size of less than or equal to 50 nm. The void volume Q of the voids with a pore size of less than or equal to 50 nm is, for example, greater than or equal to 0.035 cc / g, and may be greater than or equal to 0.04 cc / g, or greater than or equal to 0.06 cc / g. The void volume Q is, for example, less than or equal to 0.11 cc / g, and may be less than or equal to 0.10 cc / g.

[0057] The ratio (P / Q) of the void volume P to the void volume Q is preferably large. The ratio P / Q is, for example, greater than or equal to 0.22, and may be greater than or equal to 0.27. The ratio P / Q is, for example, less than or equal to 0.39.

[0058] The negative electrode active material contained in the negative electrode layer preferably has many tiny voids with a pore size of less than or equal to 100 nm. The void volume R of the voids with a pore size of less than or equal to 100 nm is, for example, greater than or equal to 0.053 cc / g, and may be greater than or equal to 0.06 cc / g. The void volume R is, for example, less than or equal to 0.16 cc / g, and may be less than or equal to 0.14 cc / g.

[0059] The ratio (P / R) of the void volume P to the void volume R is preferably large. The ratio P / R is, for example, greater than or equal to 0.14, and may be greater than or equal to 0.20. The ratio P / R is, for example, less than or equal to 0.30.

[0060] The ratio of the negative electrode active material in the negative electrode layer is, for example, 20 wt % or more, and may be 30 wt % or more, or 40 wt % or more. When the ratio of the negative electrode active material is too small, sufficient energy density may not be obtained. The ratio of the negative electrode active material is, for example, 80 wt % or less, and may be 70 wt % or less, or 60 wt % or less. When the ratio of the negative electrode active material is too large, the ionic conductivity and electronic conductivity of the negative electrode layer are likely to be relatively reduced.

[0061] If necessary, the negative electrode layer may contain at least one of an electrolyte, a conductive material, and a binder. Examples of electrolytes include electrolytes described later in "C. Battery Pack: 3. Electrolyte Layer". Examples of conductive materials include carbon materials, metal particles, and conductive polymers. Examples of carbon materials include particulate carbon materials such as acetylene black (AB) and Ketjen black (KB), fibrous carbon materials such as carbon fibers, carbon nanotubes (CNTs), and carbon nanofibers (CNFs). Examples of binders include rubber binders and fluoride binders.

[0062] The thickness of the negative electrode layer is, for example, greater than or equal to 0.1 μm and less than or equal to 1000 μm. The negative electrode layer in the present disclosure is generally used for a battery pack. C.Battery Pack

[0063] Figure 2 is a schematic cross-sectional view illustrating one example of a battery pack in the present disclosure. Figure 2 The battery pack 10 shown in the figure includes a positive electrode layer 1, a negative electrode layer 2, an electrolyte layer 3 located between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode collector 4 that collects current from the positive electrode layer 1, and a negative electrode collector 5 that collects current from the negative electrode layer 2. In the present disclosure, the negative electrode layer 2 is the negative electrode layer described above in "B. Negative Electrode Layer".

[0064] According to the present disclosure, a battery pack has a small volume change caused by charge and discharge by using the above-mentioned negative electrode layer. 1. Negative electrode layer

[0065] Since the negative electrode layer in the present disclosure is the same as described above in “B. Negative Electrode Layer”, the description thereof is omitted. 2. Positive electrode layer

[0066] The positive electrode layer contains at least a positive electrode active material. If necessary, the positive electrode layer may contain at least one of an electrolyte, a conductive material, and a binder.

[0067] Examples of positive electrode active materials include oxide active materials. Examples of oxide active materials include layered rock salt active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2 and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, spinel active materials such as LiMn2O4, Li4Ti5O 12 and Li(Ni 0.5 Mn 1.5 )O4, and olivine active materials such as LiFePO4, LiMnPO4, LiNiPO4 and LiCoPO4.

[0068] A coating containing a Li ion conductive oxide can be formed on the surface of the oxide active material. This is because the reaction between the oxide active material and the solid electrolyte (particularly a sulfide solid electrolyte) can be suppressed. Examples of Li ion conductive oxides include LiNbO3. The thickness of the coating is, for example, greater than or equal to 1 nm and less than or equal to 30 nm. For example, Li2S can also be used as a positive electrode active material.

[0069] The positive electrode active material is in the form of, for example, microparticles. 50 ) is not particularly limited, but is, for example, 10 nm or more, and may be 100 nm or more. The average particle size (D 50 ) is, for example, less than or equal to 50 μm, and may be less than or equal to 20 μm. The average particle size (D ) may be calculated, for example, by measuring using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM). 50 ).

[0070] Since the electrolyte, conductive material, and binder used in the positive electrode layer are the same as those described above in “B. Negative electrode layer,” description thereof is omitted. The thickness of the positive electrode layer is, for example, greater than or equal to 0.1 μm and less than or equal to 1000 μm. 3. Electrolyte layer

[0071] The electrolyte layer is formed between the positive electrode layer and the negative electrode layer and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolyte solution).

[0072] Examples of solid electrolytes include inorganic solid electrolytes, such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes and halide solid electrolytes, and organic polymer electrolytes, such as polymer electrolytes. Examples of sulfide solid electrolytes include solid electrolytes containing Li element, X element (X is at least one of phosphorus (P), arsenic (As), antimony (Sb), Si, germanium (Ge), tin (Sn), boron (B), aluminum (Al), gallium (Ga) and indium (In)) and sulfur (S) element. Sulfide solid electrolytes may further contain at least one of O element and halogen element. Examples of halogen elements include fluorine (F) element, chlorine (Cl) element, bromine (Br) element and iodine (I) element. Sulfide solid electrolytes may be glass (amorphous) or glass ceramics. Examples of the sulfide solid electrolyte include Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2 and Li2S-P2S5-GeS2.

[0073] The electrolyte solution preferably contains a supporting salt and a solvent. The example of the supporting salt (lithium salt) of the electrolyte solution with lithium ion conductivity includes an inorganic lithium salt, such as LiPF6, LiBF4, LiClO4 and LiAsF6, and an organic lithium salt, such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2 and LiC(CF3SO2)3. The example of the solvent used in the electrolyte solution includes cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC), and chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC). The electrolyte solution preferably contains two or more solvents.

[0074] The thickness of the electrolyte layer is, for example, greater than or equal to 0.1 μm and less than or equal to 1000 μm. 4. Other structures

[0075] The battery pack in the present disclosure preferably includes a positive electrode current collector that collects current from the positive electrode layer and a negative electrode current collector that collects current from the negative electrode layer. Examples of materials for the positive electrode current collector include stainless steel (SUS), aluminum, nickel, iron, titanium and carbon. Examples of materials for the negative electrode current collector include stainless steel (SUS), copper, nickel and carbon.

[0076] The battery pack in the present disclosure may further include a confining jig that applies a confining pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer in the thickness direction. In particular, when the electrolyte layer is a solid electrolyte layer, it is preferred to apply a confining pressure to form a satisfactory ion conduction path and a satisfactory electron conduction path. The confining pressure is, for example, 0.1 MPa or more, and may be 1 MPa or more, or 5 MPa or more. The confining pressure is, for example, 100 MPa or less, and may be 50 MPa or less, or 20 MPa or less. 5. Battery Pack

[0077] There is no particular limitation on the type of battery in the present disclosure, but it is generally a lithium ion battery. The battery in the present disclosure may be a liquid battery containing an electrolyte solution as an electrolyte layer, or an all-solid-state battery having a solid electrolyte layer as an electrolyte layer. The battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because it can be repeatedly charged and discharged, and can be used as a battery for a vehicle, for example.

[0078] The battery pack in the present disclosure may be a single cell or a stacked battery pack. The stacked battery pack may be a monopolar stacked battery pack (parallel stacked battery pack) or a bipolar stacked battery pack (series stacked battery pack). The shape of the battery pack is, for example, a coin shape, a laminated shape, a cylindrical shape, or a rectangular shape. D. Methods of Producing Active Materials

[0079] Figure 3 is a flow chart illustrating an example of a method for producing an active material in the present disclosure. Figure 3 In the production method shown in , a Na-Si alloy is first obtained by reacting a sodium (Na) source and a silicon (Si) source with each other (alloying step). Next, a silicon inclusion compound type crystalline phase is produced by heating the Na-Si alloy to reduce the amount of Na in the Na-Si alloy (silicon inclusion compound production step). At this time, a scavenger is used to remove Na in the Na-Si alloy. As a result, an active material having a large void volume X and a silicon inclusion compound type crystalline phase can be obtained.

[0080] According to the present disclosure, by using a predetermined scavenger in the silicon clathrate production step, an active material with a small volume change caused by charge and discharge can be obtained. 1. Alloying step

[0081] The alloying step in the present disclosure is a step of obtaining a Na—Si alloy by reacting a Na source and a Si source with each other.

[0082] The Si source is a particle containing at least Si. The Si source may be Si alone or an alloy of Si and any other metal. When the Si source is an alloy, the alloy preferably contains Si as a main component. The ratio of Si in the alloy is, for example, 50 atomic % or more, and may be 70 atomic % or more, or 90 atomic % or more.

[0083] The Si source is preferably a porous Si having many voids in the primary particles. In the Si source, the void volume α of the voids having a pore size of less than or equal to 50 nm is, for example, greater than or equal to 0.02 cc / g, and may be greater than or equal to 0.05 cc / g, greater than or equal to 0.10 cc / g, greater than or equal to 0.11 cc / g, or greater than or equal to 0.12 cc / g. The void volume α is, for example, less than or equal to 0.20 cc / g, and may be less than or equal to 0.19 cc / g. The BET specific surface area of ​​the Si source is, for example, greater than or equal to 20 m 2 / g, and can be greater than or equal to 25m 2 / g, or greater than or equal to 30m 2 / g. The BET specific surface area of ​​the Si source is, for example, less than or equal to 200 m 2 / g. The average particle size of Si source (D 50 ) is, for example, greater than or equal to 0.5 μm and less than or equal to 10 μm.

[0084] Examples of methods for producing Si sources (porous Si) include methods for producing alloys of magnesium (Mg) and Si (Mg-Si alloys), and then removing Mg from the Mg-Si alloys. For example, a Mg-Si alloy is obtained by heating a mixture of Mg and Si. The ratio of Mg to Si (Mg / Si) is, for example, greater than or equal to 1.0, and may be greater than or equal to 1.5, or greater than or equal to 2.0. The ratio of Mg / Si is, for example, less than or equal to 6.0. Examples of methods for removing Mg from Mg-Si alloys include methods for heating a Mg-Si alloy in an oxygen-containing inert gas atmosphere to convert the Mg in the Mg-Si alloy into magnesium oxide (MgO), and then removing MgO with an acid solution. Examples of acid solutions include aqueous solutions containing hydrochloric acid (HCl) and hydrogen fluoride (HF).

[0085] The example of the method for producing Si source (porous Si) includes producing an alloy of Li and Si (Li-Si alloy), and then removing Li from the Li-Si alloy. For example, the Li-Si alloy is obtained by mixing Li and Si. The ratio of Li to Si (Li / Si) is, for example, greater than or equal to 1.0, and can be greater than or equal to 2.0, greater than or equal to 3.0, or greater than or equal to 4.0. The ratio of Li / Si is, for example, less than or equal to 8.0. The example of the method for removing Li from the Li-Si alloy includes a method for reacting the Li-Si alloy with a Li extractant. The example of the Li extractant includes alcohols such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol and 1-hexanol, and acids such as acetic acid, formic acid, propionic acid and oxalic acid.

[0086] Examples of methods for producing a Si source (porous Si) include producing an alloy of Mg and Si (Mg-Si alloy), then removing Mg from the Mg-Si alloy, then producing an alloy of Li and Si (Li-Si alloy) from which Mg has been removed, and then removing Li from the Li-Si alloy.

[0087] The Na source contains at least Na. Examples of the Na source include metallic Na, sodium hydride (NaH), and a metallic Na dispersion obtained by dispersing particles of metallic Na in oil.

[0088] An example of a method for obtaining a Na-Si alloy by reacting a Na source and a Si source with each other includes a method of heating a mixture containing a Na source and a Si source. The heating temperature is, for example, 300°C or higher, and may be 310°C or higher, 320°C or higher, or 340°C or higher. The heating temperature is, for example, 800°C or lower, and may be 600°C or lower, or 450°C or lower. The alloying step is preferably carried out in an inert atmosphere, such as an argon (Ar) atmosphere.

[0089] The Na-Si alloy preferably has a Zintl phase. In the X-ray diffraction measurement using CuKα rays, the Zintl phase has typical peaks at positions of 2θ=16.10°, 16.56°, 17.64°, 20.16°, 27.96°, 33.60°, 35.68°, 40.22° and 41.14°. These peak positions can vary within the range of ±0.50° or ±0.30°. The Na-Si alloy preferably has a Zintl phase as the main phase. The Na-Si alloy may or may not have a crystalline phase of type I silicon inclusion compound.

[0090] Although there is no particular limitation on the composition of the Na-Si alloy, it is preferably composed of Na z Si 136 (121≤z≤151). The value z may be greater than or equal to 126, or greater than or equal to 131. The value z may be less than or equal to 141. Elements other than Na and Si may be present in the Na-Si alloy. Examples of other elements include Li, potassium (K), rubidium (Rb), cesium (Cs), barium (Ba), Ga, and Ge. 2. Silicon inclusion compound production steps

[0091] The silicon inclusion compound production step in the present disclosure is a step of producing a silicon inclusion compound type crystalline phase by heating a Na-Si alloy to reduce the amount of Na in the Na-Si alloy. The silicon inclusion compound type crystalline phase can be a crystalline phase of a type I silicon inclusion compound or a crystalline phase of a type II silicon inclusion compound. The crystalline phase of the type I silicon inclusion compound or the crystalline phase of the type II silicon inclusion compound can be obtained by changing the heating conditions as appropriate. In the silicon inclusion compound production step, a scavenger is used to remove Na in the Na-Si alloy.

[0092] Examples of scavengers include Na getter agents that react with Na vapor generated by the Na-Si alloy. The Na getter agent is, for example, placed in non-contact with the Na-Si alloy. Examples of Na getters include SiO, MoO3, and FeO. When using a Na getter agent, the silicon inclusion compound production step is preferably carried out in a reduced pressure atmosphere.

[0093] Other examples of scavengers include Na-capturing agents that receive Na by direct reaction with the Na-Si alloy. The Na-capturing agent is placed in contact with the Na-Si alloy, for example. Examples of Na-capturing agents include CaCl2, AlF3, CaBr2, CaI2, Fe3O4, FeO, MgCl2, ZnO, ZnCl2, and MnCl2. When using a Na-capturing agent, the silicon inclusion compound production step can be carried out in a reduced pressure atmosphere or in a normal pressure atmosphere.

[0094] The heating temperature in the silicon clathrate production step is, for example, 100° C. or higher, and may be 200° C. or higher, or 270° C. or higher. The heating temperature is, for example, 500° C. or lower, and may be 400° C. or lower. 3. Active Materials

[0095] The active material obtained by the above steps has a silicon inclusion compound type crystalline phase. The active material has voids within the primary particles. The preferred range of the void volume of the active material, A / I M and I B / I M For the preferred ranges of and other matters, reference may be appropriately made to the details described above in “A. Active material”. E. Method for producing negative electrode layer

[0096] The present disclosure provides a method for producing a negative electrode layer, which includes an active material production step of producing an active material by the above-mentioned method for producing an active material, and a negative electrode layer formation step of forming a negative electrode layer using the active material.

[0097] According to the present disclosure, a negative electrode layer having a small volume change caused by charging and discharging can be obtained by using the above-mentioned active material. The active material production step is the same as the step described above in "D. Method for producing active material". There is no particular limitation on the method for forming the negative electrode layer, and various methods can be used. Examples of methods for forming the negative electrode layer include a method of applying a slurry containing at least an active material to a negative electrode current collector and drying the slurry.

[0098] When the negative electrode layer is formed, pressing may be performed to press the negative electrode layer in the thickness direction. Examples of pressing include roll pressing and flat plate pressing. Regarding the preferred form of the negative electrode layer to be obtained, the details described in "B. Negative Electrode Layer" above may be appropriately referred to. F. Method of Producing a Battery Pack

[0099] The present disclosure provides a method for producing a battery pack, which includes an active material production step of producing an active material by the above-mentioned method for producing an active material, and a negative electrode layer formation step of forming a negative electrode layer using the active material.

[0100] According to the present disclosure, by using the above-mentioned active material, a battery pack with a small volume change caused by charging and discharging can be obtained. The active material production step and the negative electrode layer formation step are the same as those described above in "D. Method for producing active materials" and "E. Method for producing negative electrode layers". There is no particular limitation on the method of forming a battery pack, and various methods can be adopted. In addition to the active material production step and the negative electrode layer formation step, the method for producing a battery pack in the present disclosure may also include a positive electrode layer formation step for forming a positive electrode layer, an electrolyte layer formation step for forming an electrolyte layer, and a setting step for sequentially setting a positive electrode layer, an electrolyte layer, and a negative electrode layer. Regarding the preferred form of the battery pack to be obtained, the details described above in "C. Battery Pack" can be appropriately referred to.

[0101] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are illustrative, and anything having substantially the same configuration as the technical concept described in the claims of the present disclosure and having similar functions and effects is included in the technical scope of the present disclosure. Example 1

[0102] Si powder (Si powder without voids in primary particles; SIE23PB produced by Kojundo Chemical Laboratory Co., Ltd.) was prepared as a Si source. Na-Si alloy was produced by using a Si source and using NaH as a Na source. As NaH, NaH pre-washed with hexane was used. The Na source and the Si source were weighed to a molar ratio of 1.05:1 and mixed using a cutter. This mixture was heated in an Ar atmosphere in a heating furnace at 400°C for 40 hours to obtain a powdered Na-Si alloy.

[0103] The silicon inclusion compound production step by the solid phase method is carried out using the obtained Na-Si alloy and further using AlF3 as a Na capture agent. The Na-Si alloy and AlF3 are weighed to a molar ratio of 1:0.35 and mixed using a cutter to obtain a reaction raw material. The obtained powdered reaction raw material is placed in a stainless steel reaction vessel and heated in an Ar atmosphere in a heating furnace at 310°C for 60 hours to cause a reaction. The obtained reaction product may contain the desired active material as well as NaF and Al as by-products. This reaction product is washed with a mixed solvent of HNO3 and H2O in a volume ratio of 90:10. The by-products in the reaction product are thereby removed. The washed reaction product is filtered, and the obtained solid content is dried at 120°C for 3 hours or longer to obtain a powdered active material. Example 2

[0104] Mg powder and Si powder are weighed to a molar ratio of 2.02: 1, mixed in a mortar, and heated at 580° C. for 12 hours in a heating furnace in an Ar atmosphere so that the Mg powder and Si powder react with each other. The resulting mixture is cooled to room temperature to obtain Mg2Si in the form of an ingot. Mg2Si is crushed at 300rpm for 3 hours by a ball mill using a zirconia ball with a diameter of 3mm. Then, the crushed Mg2Si is heated at 580° C. for 12 hours in a heating furnace under a mixed gas flow of Ar and O2 with a volume ratio of 95: 5 so that the oxygen in the mixed gas and Mg2Si react with each other. The resulting reaction product may contain Si and MgO. The reaction product is washed with a mixed solvent of H2O, HCl and HF with a volume ratio of 47.5: 47.5: 5. The oxide film on the Si surface and the MgO in the reaction product are thereby removed. The washed reaction product is filtered and the resulting solid content is dried at 120° C. for 3 hours or longer to obtain powdered porous Si. An active material was obtained in the same manner as in Example 1, except that the obtained porous Si was used as a Si source instead of Si powder. Example 3

[0105] Metal Li and Si powders were weighed to a molar ratio of 4:1 and mixed in a mortar at room temperature in an Ar atmosphere for 0.5 hours to react the metal Li and Si powders with each other. Li4Si was thus obtained. The obtained Li4Si was reacted with ethanol in an Ar atmosphere. The obtained reaction product may contain Si and CH3CH2OLi. The reaction product was filtered, and the obtained solid content was dried at 120°C for 3 hours or longer to obtain powdered porous Si. The active material was obtained in the same manner as in Example 1, except that the obtained porous Si was used instead of Si powder as a Si source. Example 4

[0106] Powdered porous Si was obtained in the same manner as in Example 3. An active material was obtained in the same manner as in Example 1 except that the obtained porous Si was used as the Si source instead of Si powder and the heating conditions after adding AlF3 were changed from 310°C and 60 hours to 310°C and 120 hours. Example 5

[0107] Powdered porous Si was obtained in the same manner as in Example 3. An active material was obtained in the same manner as in Example 1 except that the obtained porous Si was used as the Si source instead of Si powder and the heating conditions after adding AlF3 were changed from 310°C and 60 hours to 290°C and 120 hours. Example 6

[0108] Powdered porous Si was obtained in the same manner as in Example 3. By using the obtained porous Si instead of Si powder as a Si source, an active material was obtained in the same manner as in Example 1. Then, the obtained active material was washed by immersing in an HF aqueous solution for 3 hours (HF washing). Example 7

[0109] Powdered porous Si (first porous Si) was obtained in the same manner as in Example 2. Powdered porous Si (second porous Si) was obtained in the same manner as in Example 3, except that the obtained first porous Si was used instead of Si powder. An active material was obtained in the same manner as in Example 1, except that the obtained second porous Si was used instead of Si powder as a Si source. Example 8

[0110] Second porous Si was obtained in the same manner as in Example 7. An active material was obtained in the same manner as in Example 1 except that the obtained second porous Si was used as the Si source instead of Si powder and the heating conditions after adding AlF3 were changed from 310°C and 60 hours to 270°C and 120 hours. Example 9

[0111] An active material was obtained in the same manner as in Example 7. Then, the obtained active material was washed by immersing in an HF aqueous solution for 3 hours (HF washing). Example 10

[0112] Except for adjusting the amounts of metal Li and Si powder, porous Si was obtained in the same manner as in Example 3. The obtained porous Si was used as an active material. Comparative Example 1

[0113] Si particles are used as Si source, and Na particles are used as Na source. Si particles and Na particles are mixed to a molar ratio of 1: 1, placed in a crucible, sealed in an Ar atmosphere, and heated at 700 ° C to obtain a Na-Si alloy. The resulting Na-Si alloy is heated at a vacuum (about 1 Pa) and 340 ° C to remove Na, thereby obtaining an intermediate of a crystalline phase with a type II silicon inclusion compound. The resulting intermediate and Li metal are weighed at a molar ratio of Li / Si=2.5, and mixed in a mortar in an Ar atmosphere to obtain an alloy compound. The resulting alloy compound is reacted with ethanol in an Ar atmosphere to form a void in the primary particle, thereby obtaining an active material. Evaluate XRD measurement

[0114] The active materials obtained in Examples 1 to 9 and Comparative Example 1 were subjected to X-ray diffraction (XRD) measurement using CuKα rays. The results confirmed that all of the active materials had a crystalline phase of type II silicon clathrate as their main phase.

[0115] The intensity of peak A at 2θ=20.09° in the crystalline phase of type II silicon inclusion complex is A The intensity of peak B near 2θ = 31.72° is represented by I B The maximum intensity at 2θ = 22° to 23° is represented by I M Indicates and determines I A / I M and I B / I M The results are shown in Table 1. Void volume measurement

[0116] The void volumes of the active materials obtained in Examples 1 to 10 and Comparative Example 1 were measured. The void volumes were measured using a mercury porosimeter. PoreMaster 60-GT (QuantaChrome Co.) was used as a measuring device, and to The results are shown in Table 1. Table 1

[0117] As shown in Table 1, the void volumes X and the void volumes Y in Examples 1 to 10 were larger than those in Comparative Example 1. A / I M and I B / I M is greater than 1 and a crystalline phase of type II silicon inclusion compound is formed.

[0118] In Comparative Example 1, Si is made into an inclusion compound (Na alloying and Na desorption) and then made porous. When the amount of Li used for pore formation increases in this case, the crystalline phase of the type II silicon inclusion compound may disappear. Therefore, the amount of Li used is limited. In Examples 2 to 9, Si is made porous and then made into an inclusion compound. In this case, the amount of Li used for pore formation can be increased, and sufficient pore formation can be achieved. When sufficiently porous Si is made into an inclusion compound at high temperature, tiny voids may disappear. In Examples 2 to 9, Si can be made into an inclusion compound at a low temperature by using a scavenger. As a result, it is presumed that the void volume X and the void volume Y in the active materials obtained in Examples 2 to 9 increase. Measurement of confining pressure increase

[0119] All-solid-state batteries were produced by using, as negative electrode active materials, the active materials obtained in Examples 1 to 10 and Comparative Example 1. The production method was as follows. (1) Production of negative electrode

[0120] The obtained active material, sulfide solid electrolyte (Li2S-P2S5 glass ceramic), conductive material (VGCF), butyl butyrate solution containing 5% by weight of PVDF binder and butyl butyrate were added to a polypropylene container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was vibrated for 30 minutes with an oscillator (TTM-1 manufactured by Sibata ScientificTechnology Ltd.). The resulting mixture was applied to the negative electrode collector (Cu foil produced by UACJ) by a doctor blade method using an applicator and dried on a hot plate at 100°C for 30 minutes. Thus, a negative electrode including a negative electrode collector and a negative electrode layer was obtained. (2) Production of positive electrode

[0121] The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2; average particle size 6μm), sulfide solid electrolyte (Li2S-P2S5 glass ceramic), conductive material (VGCF), butyl butyrate solution containing 5% by weight of polyvinylidene fluoride (PVDF) binder, and butyl butyrate were added to a polypropylene container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was vibrated for 3 minutes with an oscillator (TTM-1 manufactured by Sibata Scientific Technology Ltd.). The resulting mixture was applied to the positive electrode collector (Al foil produced by Showa Denko K.K.) by a scraper method using an applicator and dried on a hot plate at 100°C for 30 minutes. A positive electrode including a positive electrode collector and a positive electrode layer is thus obtained. The area of ​​the positive electrode is smaller than that of the negative electrode. (3) Production of solid electrolyte layer

[0122] The sulfide solid electrolyte (Li2S-P2S5 glass ceramic), a heptane solution containing a 5 wt% ratio of a butene rubber-based adhesive and heptane were added to a polypropylene container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was vibrated for 30 minutes with an oscillator (TTM-1 manufactured by Sibata Scientific Technology Ltd.). The resulting mixture was applied to a release sheet (Al foil) by a doctor blade method using an applicator and dried on a hot plate at 100°C for 30 minutes. Thus, a transfer member including a release sheet and a solid electrolyte layer was obtained. (4) Production of all-solid-state battery packs

[0123] The solid electrolyte layer for joining was placed on the positive electrode layer of the positive electrode, placed in a roll press, and pressed at 100 kN / cm at 165° C. Thus, a first laminate was obtained.

[0124] Next, the negative electrode was placed in a roller press and pressed at 60 kN / cm at 25°C. A pressed negative electrode was thus obtained. Then, the solid electrolyte layer and the transfer member for bonding were placed in sequence from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer in the transfer member were placed face to face with each other. The resulting laminate was placed in a flat uniaxial press and temporarily pressed at 100 MPa at 25°C for 10 seconds. Then, the release sheet was peeled off from the solid electrolyte layer. A second laminate was thus obtained.

[0125] Next, the solid electrolyte layer for bonding in the first laminate and the solid electrolyte layer in the second laminate were placed facing each other, placed in a flat uniaxial press, and pressed at 200 MPa at 120° C. for 1 minute. Thus, an all-solid-state battery was obtained. (5) Measurement of confining pressure increase

[0126] The obtained all-solid-state battery pack was charged and the increase in confining pressure was measured. The test conditions were a confining pressure of 5 MPa (fixed), charging at 0.1C and a cut-off voltage of 4.55 V. The confining pressure at 4.55 V was measured, and the increase in confining pressure compared to the state before charging was determined. The results are shown in Table 2. The results of the increase in confining pressure in Table 2 are relative values ​​when the results in Comparative Example 1 are regarded as 100. Table 2

[0127] As shown in Table 2, it was confirmed that the amount of increase in confining pressure was smaller in Examples 1 to 10 than in Comparative Example 1. This is probably because the negative electrode active materials obtained in Examples 1 to 10 had many minute voids having a pore size of less than or equal to 10 nm. Void volume measurement

[0128] By using the active materials obtained in Examples 1 to 3, 6 and 10 and Comparative Example 1, a pressed negative electrode was obtained in the same manner as described above in "Measurement of the increase in confining pressure". The void volume of the negative electrode active material in the pressed negative electrode was determined. The method for measuring the void volume is the same as described above. The results are shown in Table 3. Table 3

[0129] As shown in Table 3, it was confirmed that the void volume of the negative electrode active material after pressing was larger in Examples 1 to 3, 6, and 10 than in Comparative Example 1.

Claims

1. A silicon-containing active material, wherein The active material has voids within primary particles, and The void volume X of the voids having a pore diameter of 10 nm or less is 0.015 cc / g or more. 2 . The active material according to claim 1 , wherein the void volume X is less than or equal to 0.09 cc / g. 3 . The active material according to claim 1 , wherein a void volume Y of voids having a pore diameter of 50 nm or less in the voids is greater than or equal to 0.05 cc / g and less than or equal to 0.25 cc / g. 4 . The active material according to claim 3 , wherein a ratio (X / Y) of the void volume X to the void volume Y is greater than or equal to 0.17 and less than or equal to 0.

41. 5 . The active material according to claim 1 , wherein a void volume Z of voids having a pore diameter of 100 nm or less in the voids is greater than or equal to 0.05 cc / g and less than or equal to 0.40 cc / g. 6 . The active material according to claim 5 , wherein the ratio of the void volume X to the void volume Z (X / Z) is greater than or equal to 0.10 and less than or equal to 0.

34. 7 . The active material according to claim 1 , wherein the active material has a crystalline phase of type II silicon clathrate.

8. The active material according to claim 7, wherein: In X-ray diffraction measurement using CuKα rays, a peak A at 2θ=20.09°±0.50° and a peak B at 2θ=31.72°±0.50° were observed as peaks of a crystalline phase of a type II silicon clathrate; and When the intensity of peak A is I A , the intensity of peak B is I B , and the maximum intensity at 2θ = 22° to 23° is I M When A / I M is greater than or equal to 1.75 and less than or equal to 10, and I B / I M is greater than or equal to 1.35 and less than or equal to 7.

9. The active material according to claim 1 or 2, wherein the active material has a crystal phase of diamond-like silicon.

10. A negative electrode layer comprising an active material containing silicon, wherein The active material has voids within primary particles, and The void volume P of the voids having a pore diameter of 10 nm or less is 0.015 cc / g or more. 11 . The negative electrode layer according to claim 10 , wherein the void volume P is less than or equal to 0.031 cc / g. 12 . The negative electrode layer according to claim 10 , wherein a void volume Q of voids having a pore diameter of 50 nm or less in the voids is greater than or equal to 0.035 cc / g and less than or equal to 0.11 cc / g. 13 . The negative electrode layer according to claim 12 , wherein a ratio (P / Q) of the void volume P to the void volume Q is greater than or equal to 0.22 and less than or equal to 0.

39. 14 . The negative electrode layer according to claim 10 , wherein a void volume R of voids having a pore diameter of 100 nm or less in the voids is 0.053 cc / g or more and 0.16 cc / g or less. 15 . The negative electrode layer according to claim 14 , wherein a ratio of void volume P to void volume R (P / R) is greater than or equal to 0.14 and less than or equal to 0.

30.

16. A battery pack comprising: The negative electrode layer according to claim 10 or 11; a positive electrode layer; and An electrolyte layer is provided between the positive electrode layer and the negative electrode layer.

17. A method for producing the active material according to claim 1 or 2, the method comprising: Obtaining a Na—Si alloy by reacting a sodium source and a silicon source with each other; and The silicon clathrate type crystalline phase is produced by heating the Na-Si alloy to reduce the amount of sodium in the Na-Si alloy, wherein Producing the silicon inclusion type crystalline phase uses a scavenger to scavenger sodium from the Na—Si alloy.

18. A method for producing a negative electrode layer, the method comprising: Producing an active material by the method for producing an active material according to claim 17; and A negative electrode layer is formed by using the active material.

19. A method for producing a battery pack, the method comprising: Producing an active material by the method for producing an active material according to claim 17; and A negative electrode layer is formed by using the active material.